A Causal-Comparative Study of Inquiry-Based Science Learning Based on Levels of Students' Cognitive Learning Outcomes: Systematic Review - Bani Nugroho; Zulfiani Zulfiani* (Jurnal Pendidikan Sains Indonesia, 2021)
The effect of inquiry-based learning models on cognitive learning outcomes has been discussed for a long time. However, in local research, this effect is more focused on comparing inquiry-based learning models with traditional learning models. Given such studies' rarity, this study seeks to compare the various inquiry levels to cognitive learning outcomes. This study aims to determine the differences in students' cognitive aspects between structured inquiry and guided inquiry-based science learning models. The research method used is a causal-comparative method, with a sample search technique in the systematic review. The sample used is secondary data in the form of undergraduate theses that have passed the selection and come from the Biology Education program at least accredited B with the research theme of the effect of inquiry learning models on high school students' cognitive learning outcomes. The research findings reveal significant differences in cognitive learning outcomes between the structured inquiry (SI) and guided inquiry (GI) learning model. The processing is more complicated in the GI learning model, allows students to perform better in learning outcomes than the SI learning model. Significant differences were supported by calculating the effect size in this study. The effect size in studies that apply the SI learning model belongs to the medium category. Meanwhile, the effect size in studies using the GI learning model belongs to the large to extremely large categories